2019
DOI: 10.1002/jms.4424
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of stable and reactive metabolites of piperine formed on incubation with human liver microsomes

Abstract: Black pepper, though commonly employed as a spice, has many medicinal properties.It consists of volatile oils, alkaloids, pungent resins, etc., of which piperine is a major constituent. Though safe at low doses, piperine causes alteration in the activity of drug metabolising enzymes and transporters at high dose and is known to precipitate liver toxicity. It has a potential to form reactive metabolite(s) (RM) owing to the presence of structural alerts, such as methylenedioxyphenyl (MDP), α, β-unsaturated carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
4
6
0
Order By: Relevance
“…Its MS/MS spectrum (Figure 7B) showed three indicative product ions at m/z 201.0544, 135.0440, and 110.0602, which indicated that dehydrogenation had occurred on the piperidine ring. This metabolite was similar to one reported previously 19 …”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Its MS/MS spectrum (Figure 7B) showed three indicative product ions at m/z 201.0544, 135.0440, and 110.0602, which indicated that dehydrogenation had occurred on the piperidine ring. This metabolite was similar to one reported previously 19 …”
Section: Resultssupporting
confidence: 91%
“…The MS/MS spectrum of their [M + H] + ions (Figure 5C) showed two indicative product ions at m/z 201.0545 and 102.0911, which indicated that hydroxylation occurred on the piperidine ring. These compounds were similar to previously reported metabolites 19 …”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations